2014
DOI: 10.2139/ssrn.2489468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Innovation on Employment in Low-Income Countries: A Mixed-Method Systematic Review

Abstract: We conduct a meta-analysis of the effect-size estimates from 9 empirical studies and a narrative synthesis of the qualitative evidence from 53 qualitative studies on the relationship between innovation and employment in low-income countries (LICs). The meta-analysis reveals a positive but small effect, with evident bias in favour of skilled-labour employment. Both meta-analysis and narrative synthesis findings indicate that innovation's effects on employment in LICs tend to be larger when: (i) the evidence is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 56 publications
0
16
0
1
Order By: Relevance
“…Ugur and Dasgupta synthesised 115 studies on the effect of corruption on economic growth. In this meta-analysis, they found that a unit increase in the corruption perception index leads to a loss of growth of per capita GDP of 0.59 percentage points [ 12 ]. We use this estimate to calculate the potential growth of per capita GDP achievable in the absence of any perception of corruption using Transparency International’s index.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ugur and Dasgupta synthesised 115 studies on the effect of corruption on economic growth. In this meta-analysis, they found that a unit increase in the corruption perception index leads to a loss of growth of per capita GDP of 0.59 percentage points [ 12 ]. We use this estimate to calculate the potential growth of per capita GDP achievable in the absence of any perception of corruption using Transparency International’s index.…”
Section: Methodsmentioning
confidence: 99%
“…We assume that the allocation of government resources does not change and that each sector including the health sector continues to receive the same proportion of funding with the increased availability of resources as corruption and IFF are reduced. This assumption is reasonable given the evidence that reduced corruption, will lead to economic growth [ 12 ] and improved governance results in increased spending on, and provision of, social services include health care services [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations